Percepções de professores do fundamental II sobre sua formação e atuação. - Lima, Joelma Silveira Goularte de (2017)
The research developed with teachers of Elementary School II (EF II), aims to identify the perceptions of teachers about their formation and performance. The text is based on theoretical references, which deal with teacher training and professionalism, and especially Freire's theory (Freire, 2007, 2010, 2014, 2016), revisiting the concepts of dialogicity, action-reflection and awareness. It is based on the assumption that the pedagogical work is constituted by the teachers' perception of the context and the school culture, of the management, of their relation with the student, of the social valorization of the profession, of their social history of life and of their Training and acting throughout the professional career. The focus of the study focuses on the perceptions of EF II teachers, because there is little research on this teaching stage, and they are directed towards understanding the formation and the teaching performance. The qualitative research was developed in three stages: bibliographic survey on the theme in question; Interviews with managers, students and teachers in public schools of the municipal network of Santos and in-depth interviews with four (04) teachers from four different schools in order to deepen understanding about the data collected earlier. Through the content analysis technique (BARDIN, 2007), data were organized in the following dimensions of analysis - Teacher Training and Teaching - and their respective categories of analysis - Initial and Continuing Education, Political Pedagogical Project (PPP) and Difficulties Of Teaching -, as well as the sense units, since they understand the perceptions of EF II teachers on the subject matter. The results point to the need to review: 1st the initial training of teachers in the different undergraduate courses - in order to know their trajectory of formation and to understand how (re) constitutes the personal and professional identity; Moreover, to favor a better articulation between theory and practice; 2º ongoing formation - seeking to foster, for HTPC, more participative practices and exchanges of experiences in order to promote moments of dialogue, action-reflection and awareness; 3º the PPP - so that it is possible to encourage the participation of teachers and other professionals of the School in its (re) construction, through planned actions, executed and evaluated continuously; 4º the relationship of teachers with students and their families - so that it is strengthened and encouraged by the School (managers, teachers and students), thus seeking to minimize many of the difficulties in teaching work. It is also considered that effective studies and policies of action need to be improved and guaranteed, including quality training and improvements in salary and working conditions.